PENDIDIKAN ISLAM ANAK USIA DINI BERBASIS AL-QUR’AN - Muhammad Yusuf; Romelah Romelah; Nurul Humaidi (Jurnal Panrita, 2024)
Discourse on Qur'an-based Islamic education for early childhood is increasingly coloring the world of education. Children will grow into individuals with character if they can grow in a good environment, so that the innate nature of every child born pure will develop optimally. The objectives of this research are (1) To understand M. Quraish Shihab's thoughts in the Al-Misbah interpretation about Islamic education for early childhood in Surah Al-Furqan verses 63-70; (2) To understand the implications of the verses of Surah Al-Furqan verses 63-70 on the development of Islamic Education for Early Childhood. This type of research is qualitative research, with the type of research used being library research. The primary data source used in this study is the al-Mishbah interpretation. In Surah Al-Furqan verses 63-74, Qur'an-based Islamic education for early childhood is described, such as accustoming children to interact with others with full humility, not being harsh, not hurting others, answering the greetings of ignorant people with words that lead to safety, habituation of worship, always praying, not being stingy, not disturbing others and guarding oneself from immoral/sinful acts. Qur'an-based Islamic education for early childhood has an effective influence on every action taken by each child. It can influence the faith, Islam, and goodness done by every child.